Preparation and characterization of rutile TiO 2 films - Narksitipan S. (2014)
Rutile titanium dioxide TiO 2 films were prepared by calcination for 4 h at temperatures in the range 550-700°C. Their structure and crystalline nature were investigated by X-ray diffraction (XRD), selected area electron diffraction (SAED) and Raman spectroscopy. After film preparation at 700°C, rutile TiO2 with a tetragonal structure was detected. Raman spectra displayed centered bands at 235, 440 and 603 cm -1, corresponding to the rutile structure of TiO 2. The intensity of rutile TiO 2 increased with an increase in the calcination temperatures. The Raman spectra agree very well with SAED patterns. In addition, the characterization of rutile films with (scanning electron microscopy) SEM and atomic force microscopy (AFM) showed a surface roughness and dense particles with an angular shape.